A study on the effect of media on gender identity differences between Mothers and daughters: A Study in Rasht - Mohammad Amin Kanani; mehdi hamidifar; abouzar ghorbani (توسعه اجتماعی)
The aim of this study was to examine the differences in gender identity of the mothers and daughters and the role of mass media on these differences. The theoretical framework was based on Jenkins' and Giddens' perspectives on gender identity and its transformations as a social process. This research conducted using a quantitative survey method with a sample of 384 residents of Rasht and using a proportionate stratified sampling method in 5 regions of the city. The results showed that mothers have higher gender identity than the daughters. The identity differences between the two generations of mothers and daughters are observed in various aspects of the rate and motives of using the national media, satellite and virtual social networks. However, identity differences were not observed between the two generations in terms of Internet use. It can be concluded that the mass media is less effective on gender identity of mothers than daughters. Mothers as elder and traditional generation, have a more formidable identity than their daughters, because girls are more subjected to shifts in identity under the influence of the media.